Life Skills of Junior High School Teachers in Coastal, Rural and Urban Areas in Albay, Philippines - Cabiles, Roldan C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This qualitative phenomenological study investigates the lived experi-ences of teachers in rural, urban, and coastal areas of Albay, Philippines, highlighting the challenges and skills that shape their professional lives. Despite the critical role of teachers in education, little research has fo-cused on how geographical context influences their experiences. In-depth interviews and participant observation were employed to gather data from teacher-participants. The study utilized the phenomenologi-cal frameworks of Husserl and Heidegger to analyze the data and cap-ture the essence of the participants' experiences. The findings reveal common life skills among teachers, including adaptability, effective communication, interpersonal skills, pedagogical skills, and practicality. Both rural and urban teachers demonstrated digital literacy, while competitiveness was more pronounced in urban settings. Financial lit-eracy emerged as a strength among rural and coastal teachers, likely due to fewer distractions that lead to excessive spending. Urban teach-ers were found to be more susceptible to overspending due to the influ-ence of commercial establishments and entertainment options in their environments. These outcomes underscore the importance of under-standing how geographical context impacts teachers' experiences and skills, providing insights that can inform educational policy and prac-tice.